Weather variability associated with Aedes (Stegomyia) aegypti (Dengue vector) oviposition dynamics in Northwestern Argentina - Estallo, Elizabet Lilia (2015)
Fil: Estallo, Elizabet Lilia. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas, Fı́sicas y Naturales; Argentina.